World trends in library education - Bramley, Gerald (London : Bingley, 1975)
The intention of the present work is to examine some of the implications of this rapid growth in the number of school library schools.
Includes bibliographical references and index.
aia 28/01/2018
Loans
Keywords: Library education; Librarianship